Measurement Indicators of State Performance: A Critical Review - OZOANI, Judith Amanda; MADUBUEGWU, Chibuike E (Socialscientia: Journal of Social Sciences and Humanities, 2025)
State capacity and performance across the world are periodically reviewed to measure commitment to espoused targets of human development and economic growth. In this vein, indicators emerge as tools for assessment and index however depleted with methodological limitations. In cognizance of this reality, this study assess critically globally acclaimed measurement indicators and rankings. From qualitative design, the paper revealed that inspite of the import of measurable indicators in their classifications there are still concerns in inaccuracies, errors in measurement and misleading data. From these findings, the paper recommends for transparency and clarity in the use of indicators as measurement institutions subject their procedures and methodology to public scrutiny among other measures to bolster the value of indicators and its generalizations for wider acceptance and use.